Correlation Between Visual Acuity and Severity Stages of Primary Angle-Closure Glaucoma - Nurul Syifa Kurnia; Kadri, Husnil; Ilahi, Fitratul (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2024)
Introduction: Primary Angle Closure Glaucoma (PACG) is a significant cause of irreversible blindness worldwide. It is caused by the closure of the drainage angle in the eye, leading to increased intraocular pressure. This study investigates the relationship between PACG severity, as measured by cup-to-disc ratio (CDR), and visual acuity in patients with PACG. Objective: The primary objective is to assess the correlation between PACG severity stages, measured by CDR indicative of glaucomatous cupping, and visual acuity in PACG patients. Methods: Conducted as a cross-sectional observational study, this research took place at the Ophthalmology Outpatient Clinic of RSUP Dr. M. Djamil Padang. The study enrolled 50 patients meeting clinical criteria, and data were subjected to Spearman's correlation test, with significance set at p<0.05. Results: The majority of PACG patients (54%) either did not experience or had not experienced visual impairment, and most were classified under moderate PACG (64%). Bivariate analysis revealed a significant positive correlation between visual acuity and PACG severity based on CDR (r=0.709). Conclusion: This study establishes a significant positive correlation, indicating that greater CDR, reflecting increased PACG severity, is associated with poorer visual acuity. Recognizing this association is crucial for developing targeted interventions and preventing irreversible visual loss in PACG patients.